Twenty-first-century African and Asian Migration to Europe and the Rise of the Ethno-topographic Narrative - Nelson González Ortega; Olga Michael (Studies in 20th & 21st Century Literature, 2022)
The first two decades of the twenty-first century have witnessed a rise in the publication of narratives concerning contemporary African and Asian migration to Europe, written individually or collectively, by Asian, African and/or European authors. While scholarly attention has increasingly turned to these texts, our purpose is to further investigate them from a pan-European perspective and to propose a model for their analysis as a distinct literary genre. We therefore introduce the "ethno-topographic narrative" to define, classify and systematically analyze twenty-first-century migration narratives published in Europe in relation to theory, method, corpus, generic type, individual or collective authorship, border and periphery/center, literal and figurative spaces, and multi-voiced modes of narration, including the gaze of the migrant, among other literary and taxonomic criteria. Focusing on five representative samples from Germany, Sweden, Italy, the UK and Greece, we argue that the new geopolitically-charged genre to which these texts belong constitutes a dynamic part of European literatures that attempts to unsettle the monolithic European canon, rejecting, as it does so, the label of the “exotic” text displaying “foreign” characters. Our approach is grounded on the implications of the three components of ethno-topographic (ethnos, topos, graphein), which enable a tripartite form of literary analysis.
Keywords: migration narratives; Asian and African migration; Europe; refugee and migration crisis; ethno-topographic narratives